If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 8(1 + -2x) = 27 -6 + (1 * 8 + -2x * 8) = 27 -6 + (8 + -16x) = 27 Combine like terms: -6 + 8 = 2 2 + -16x = 27 Solving 2 + -16x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -16x = 27 + -2 Combine like terms: 2 + -2 = 0 0 + -16x = 27 + -2 -16x = 27 + -2 Combine like terms: 27 + -2 = 25 -16x = 25 Divide each side by '-16'. x = -1.5625 Simplifying x = -1.5625
| 9y+8+7=-26 | | (x+5)2=(2x)2 | | -6x-6=7x+33 | | 4(3y+2)=-28 | | -.4x+25=0 | | 3y=155-2x | | 1-3y=3-4y | | 4w-3w+4=-4+7 | | 13x+72= | | a-12+5=-12 | | 6-9n+5n=16-90 | | 9*x=88 | | x+45=6x | | 3(c-2)+8=6+c-4 | | 3x+1=3x+0 | | 2x+3y=155 | | 9.8.2x=96 | | 2z-6z=-25 | | 20=22-d | | -7(9-5a)=-23 | | 3p.9=24 | | -4+3(18-9m)= | | x(x+4)+28=(x-1)(x+8) | | 5=6p-1 | | 2x(3x+x^2)-2x^2=136 | | 5=s-6 | | -(x)whenx=8 | | 63x^2-44x=-5x+60 | | j-20=-23 | | -p+4(3p-2)+5= | | (x*5)+21(1-x)=10 | | 16i+z^2=0 |